Picosecond Q-Switched 1064/532 nm Laser in Tattoo Removal: Our Single Center Experience - Luigi Bennardo; Giovanni Cannarozzo; Federica Tamburi; Cataldo Patruno; Eugenio Provenzano; Steven Paul Nisticò (Applied Sciences, 2021)
Background: Tattoo removal is becoming increasingly popular, and Q-switched lasers represent the gold standard in the treatment of this condition. In this study, we report our experience with a new Q-switched picosecond laser device, evaluating its effectiveness and safety. Methods: A total of 34 patients asking for tattoo removal were consecutively enrolled in this open study. The clinicians decided on operating settings based on the Fitzpatrick phototype, the type of tattoo, and the tattoo location. A maximum of seven sessions, with a minimum interval of eight weeks between each session, were performed. At the six month follow-up visit following the last treatment session, patient satisfaction was assessed using a visual analogue scale and two dermatologists evaluated the aesthetic outcome based on pictures taken before and after treatment. Results: A total of 34 patients were included and analyzed: 17 females (50%) and 17 males (50%). The mean patient age was 43.6 ± 11 years. Participants’ Fitzpatrick skin type ranged from II to IV. The mean number of treatment sessions performed was 3.3 ± 2.0 per patient. Over 40% of patients showed complete removal of the tattoo, with most of the patients indicating satisfaction with the treatment. Conclusions: The Q-switched 1064/532 nm laser may be considered the gold standard treatment for tattoo removal. Picosecond pulses seem to guarantee fewer sessions and excellent results when compared to other laser systems in tattoo removal.